Pancreatoduodenectomy for pancreatic head tumors in the elderly – Systematic review and meta-analysis. (September 2018) - Pędziwiatr, Michał; Małczak, Piotr; Mizera, Magdalena; Witowski, Jan; Torbicz, Grzegorz; Major, Piotr; Pisarska, Magdalena; Wysocki, Michał; Jankowski, Miłosz; Rubinkiewicz, Mateusz; Lasek, Anna; Kulawik, Jan; et al.
Abstract: The age at which patients are undergoing pancreatoduodenectomy is increasing worldwide. The data on the outcome of this surgical procedure in the elderly is constantly expanding. This meta-analysis aims to assess the safety of pancreatoduodenectomy in elderly population, primarily focusing on morbidity and mortality. We searched the Medline, Embase and Cochrane databases to identify eligible studies. The most recent search was performed on 10th April 2017. Inclusion criteria were: (1) comparison of the characteristics and perioperative outcomes of older patients versus younger patients undergoing pancreatoduodenectomy; (2) objective evaluation of mortality or overall morbidity; and (3), publication in English. Exclusion criteria were: (1) a lack of comparative data; (2) a lack of primary outcomes or insufficient data to analyze; (3) a focus on procedures other than pancreatoduodenectomy; or (4), the impossibility of extraction of data specifically concerning pancreatoduodenectomy. Primary outcomes were overall morbidity and mortality. Secondary outcomes analyzed postoperative complications, R0 rate and length of hospital stay. 45 eligible studies were chosen, with a combined total of 21, 295 patients. Older patients compared to younger patients had a higher risk of death (2.26% vs. 4.54%; RR: 2.23; 95% CI 1.74–2.87) and a higher complication rate (47.23% vs. 39.35%; RR: 1.17; 95% CI 1.12–1.24). There were no differences in pancreatic fistula occurrence (p = 0.27), bile leakage (p = 0.81), postoperative hemorrhage (p = 0.08), or R0 rate (p = 0.92). Our review confirms, that in the case of pancreatoduodenectomy, advanced age is a risk factor for increased non-surgical morbidity and, by extension, higher mortality. Highlights: Pancreaticoduodenectomy in older patients compared to younger patients is associated with a higher risk of death and a higher complication rate. There are no differences in pancreatic fistula occurrence, bile leakage, postoperative hemorrhage or R0 rate. Age should never be the sole contraindication to surgery.